Evangelical Christianity and democracy in Africa - Ranger, T. (Evangelical Christianity and democracy in the Global South, 2008)
One of four projected volumes to emerge from a massive Pew-funded study that sought to answer the question: What happens when a revivalist religion based on scriptural orthodoxy participates in the volatile politics of the Third World? This book considers the case of Africa.